A Baicalin Liposome-Based Temperature-Sensitive Hydrogel for Treating Ultraviolet-Induced Skin Damage - Liu X; Shu W; Zhong Q; Zeng A; Zeng Y; Gu H; Chen P; Li X (International Journal of Nanomedicine, 2025)
Xing Liu,1 Wenlin Shu,1 Qingrui Zhong,1 Anqi Zeng,2 Yong Zeng,1 Huan Gu,3 Ping Chen,2 Xiaofang Li1 1State Key Laboratory of Southwestern Chinese Medicine Resources, School of Pharmacy, Chengdu University of Traditional Chinese Medicine, Chengdu, 611137, People’s Republic of China; 2Translational Chinese Medicine Key Laboratory of Sichuan Province, Sichuan Academy of Chinese Medicine Sciences, Chengdu, 610041, People’s Republic of China; 3College of Pharmacy and Food, Southwest Minzu University, Chengdu, 610225, People’s Republic of ChinaCorrespondence: Ping Chen; Xiaofang Li, Email 284529046@qq.com; lixiaofang@cdutcm.edu.cnPurpose: Prolonged exposure of the skin to ultraviolet (UV) rays from sunlight causes oxidative damage to skin cells, and prolonged exposure to UV can lead to severe sunburn and skin aging, which may increase the risk of skin cancer. Numerous natural products have been used to treat UV-induced skin damage. Baicalin (BA) has excellent antioxidant properties; however, its poor solubility hinders its direct application. Therefore, suitable formulations for dermal administration must be developed.Methods: We designed a temperature-sensitive gel drug delivery system based on baicalin liposome (BA-LP), which was first constructed using lecithin loaded with insoluble BA. Subsequently, an injectable hydrogel (BA-LG) with temperature-sensitive properties was constructed using BA-LP and chitosan (CS) with β-glycerophosphate tetrahydrate (β-GP) as a crosslinking agent.Results: BA-LP had homogeneous particle size, high EE, and good stability. BA-LG could be gelled within 2 min at 37 °C and had good spreading, adhesion, and injectability properties. The in vitro release results showed that BA-LG had a significantly slower release effect, with a cumulative release of 60% at 24 h. The effects of BA-LG on skin keratinocyte HaCaT cells were evaluated using the CCK8 method and transwell co-culture, and the results showed good cell activity and a high survival rate, indicating that the hydrogel has good biosafety. In the UVB-induced skin injury mouse model, BA-LG showed significant effects by increasing superoxide dismutase (SOD) activity, decreasing malondialdehyde (MDA) damage, and inhibiting the expression of inflammatory factors IL-6, PGE2, and TNF-α, and demonstrated a superior therapeutic effect. The analysis of histopathological sections of the skin stained with H&E and Masson revealed results consistent with those observed on the mice.Conclusion: In summary, our results suggest that BA-LG, a temperature-sensitive gel based on baicalin liposomes, has good therapeutic efficacy and potential applications in the treatment of UVB-induced skin damage. Keywords: baicalin, temperature sensitivity, liposome, hydrogel, UV damage, antioxidant